Keefektifan Metode Modeling Simbolik Berbantu Media Wayang Kartun Profesi Terhadap Kemampuan Berbahasa dan Keterampilan Bercerita - Elyasari, Siti; Buchori, Achmad; Sulianto, Joko (Universitas PGRI Semarang, 2023)
Teachers are required to be able to apply creative and innovative learning methods by utilizing media so that they can help develop students' language skills and storytelling skills. This study aims to determine the effect, learning completeness, and average difference of the symbolic modeling method assisted by professional wayang cartoon media on language skills and storytelling skills. The methods used include observation, interviews, and documentation. The results showed that the symbolic modeling method assisted by professional wayang cartoon media had an effect on language skills and storytelling skills, in terms of the multivariate test table and the table test of between subject effects on the manova test with each Sig. 0.000 0.05. The learning completeness test obtained a sig value. 0.002 on language skills and Sig. 0.032 on storytelling skills, because the value of Sig. 0.05, it was concluded that the percentage of students who got posttest scores â‰¥ 75 was more than 75%. The average difference test obtained sig. 0.039 on language skills and sig. 0.001 on storytelling skills, because the value of Sig. 0.05 concluded that there is a difference in the mean of the two groups. The average N-Gain Score test is 0.71 for language skills, which is included in the high category, which means that interpretation is quite effective, and 0.67 for storytelling skills included in the moderate category, the interpretation is quite effective.